2001
DOI: 10.1046/j.1523-1739.2001.015002467.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Corridors: a Genetic Approach

Abstract: The effectiveness of corridors in maintaining dispersal in fragmented landscapes is a question of considerable conservation and ecological importance. We tested the efficacy of corridors as residual landscape structures in maintaining population structure in the red-backed vole ( Clethrionomys gapperi ), a closed-canopy specialist, and the deer mouse ( Peromyscus maniculatus ), a habitat generalist. In coniferous forests managed for timber production in northeastern Washington, we sampled pairs of populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
125
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(130 citation statements)
references
References 45 publications
1
125
0
4
Order By: Relevance
“…Persistence of wide-ranging species of conservation concern in patchy habitat strongly depends on habitat quality and the ability of animals to move between habitat patches (Fahrig, 2003) as well as corridors for migration to allow for movement (Hale et al, 2001;Mech & Hallett, 2001). Therefore, the identification of dispersal events between source and isolated populations may aid conservation and habitat restoration efforts in gaining a better understanding of population connectivity and in determining favourable migration routes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistence of wide-ranging species of conservation concern in patchy habitat strongly depends on habitat quality and the ability of animals to move between habitat patches (Fahrig, 2003) as well as corridors for migration to allow for movement (Hale et al, 2001;Mech & Hallett, 2001). Therefore, the identification of dispersal events between source and isolated populations may aid conservation and habitat restoration efforts in gaining a better understanding of population connectivity and in determining favourable migration routes.…”
Section: Introductionmentioning
confidence: 99%
“…Now referred to as the "discontinuous distribution", this area is being managed as a linkage to support temporary occupancy or movement between the continuous ranges to the north and the LSCR (Ministry of Natural Resources, 2009) (Figure 1). Between 1974 and2009, the population in PNP, representing roughly one quarter of the most intact habitat in the LSCR, declined at approximately 4% per year and became increasingly isolated from neighbouring ranges (Patterson et al, 2014). Although PNP's population has recently been described as extirpated (Bergerud et al, 2015), an animal was observed in the north end of the Park in the spring of 2015 and an aerial survey completed in 2016 estimated that 55 (95% CI: 13-227) animals still inhabit the mainland and nearshore islands in the LSCR (Shuter et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…When effective, corridors can reverse the trend towards diminished genetic and demographic conditions and thereby reduce the peril of extinction while protecting, perhaps enhancing, the biodiversity of the region [95,96]. Although the efficacy of wildlife corridors to promote dispersion of plants and animals is a contentious issue [97,98], there are many recent empirical studies that indicate they can be effective dispersal paths for species between isolated habitats [99][100][101][102][103]. Alternatively, the modeling results of Falcy and Estades [104] "indicate that, for a given amount of habitat, patch enlargement can increase population size more than the establishment of biological corridors."…”
Section: Eco-evolutionary Conservation: a Beginningmentioning
confidence: 99%
“…Animals and plants should have more opportunities to move among patches, thus maintaining genetic diversity in their populations and lessening the likelihood of the random extinction of small isolated populations (Beier and Noss, 1998;Mech and Hallett, 2001;Lemckert et al, 2005). Corridors may promote not only the biodiversity of plants and animals, but also their biological interactions such as pollination and seed dispersal (Tewksbury et al, 2002;Kirchner et al, 2003).…”
Section: Corridors Matrix and Connectivitymentioning
confidence: 99%